A McAb-Based Direct Competitive ELISA to Detect O:9 Salmonella Infection in Chicken - Xia, Zemiao; Geng, Haopeng; Cai, Yuan; Wang, Yaonan; Sun, Daquan; Zhang, Jian; Pan, Zhiming; Jiao, Xin'an; Geng, Shizhong (Frontiers in Veterinary Science, 2020)
Salmonella enteritidis and Salmonella pullorum belonging to Group O9Salmonella are major causative agents of infectious diseases in chicken. O9 antigen as a part of lipopolysaccharide (LPS) is a predominant detected target for Salmonella infection. To identify the infection, an anti-O9 monoclonal antibody (McAb)-based direct competitive enzyme-linked assay (O9 Dc-ELISA) was developed after constraints were optimized; the establishment and application of O9 Dc-ELISA, compared to two commercial kits and plate agglutination test (PAT), showed that O9 Dc-ELISA could screen out more positive samples than the PAT method could and produce the same agreement rates with commercial kits in terms of sensitivity in addition to strong specificity to clinical serum samples.